PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN - Yudantari, Adelia; Andarwati, Andarwati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Employee performance is one of the key factor for companies to attain their goals. Therefore, they make efforts to improve it, giving reward and punishment to name one, but the expected improvement is not optimal. The objective of this research is to identify the effect of reward and punishment on the performance of the employees of Bank Sinarmas Syariah in East Java. Through this quantitative research, explanations regarding the influence of the independent variables on the dependent one shall be provided. The data of this study was harvested from Likert-scaled questionnaires distributed to the bank’s employees. The population of this research is the employees of Bank Sinarmas Syariah in Malang, Surabaya, and Kediri. Using saturated sampling, 60 people were selected as the respondents. The results of the multiple linear regression analysis performed in SPSS have led to findings that both reward and punishment partially have positive and significant impact on employee performance. Therefore, Bank Sinarmas Syariah in East Java should apply the reward and punishment system fairly and objectively so that their impacts on employee performance are stronger.